Tweet of the town: A case study of Thailand - Kamolchanok Piriyawarangkul (2018)
Copyright 2015 © ACM. In this work, we developed a system that allows t user to search and observe the geographic distrib of different Tweet hashtags, namely Tweet-of-The Map. The system also allows the user to export th searched results along with snapshots of their geographic distribution for further analysis. Our fi developed prototype covers the entire area of Tha which is divided into six geographic regions; north northeastern, central, eastern, western, and sout regions. Twitter API was utilized to harvest Twitte hashtags of the previous seven days. The system a graphic information to display the amount of hashtags tweeted (used) in each of the six differe regions of Thailand on a map as well as bar chart system allows three different Hashtags to be sear and displayed simultaneously. The system can be in many domains, for example, it can be used as rating system for products or services, it can be p a recommendation system, and it can also be a to social science research and related fields.